IS COMPANY PERFORMANCE INFLUENCED BY SUPPLY CHAIN ORIENTATION? INSIGHT FROM HALAL SMES IN KAZAKHSTAN - Usmanova, Kamila; Sumarliah, Eli; Khan, Midrar Ullah; Mousa, Kawther (IJIBE (International Journal of Islamic Business Ethics), 2022)
This research investigate the relationship between company performance and supply chain orientation elements in halal small and medium-sized enterprises (SMEs). The advised supply chain orientation model combines three elements to identify company performance, i.e., top management support, credibility, and commitment. 511 halal SMEs in Kazakhstan were examined; 266 responses were acquired and tested using the SEM-PLS method. The findings reveal that supply chain stakeholders’ credibility has the most significant influence on company performance in the light of halal SMEs. At the same time, commitment and top management support display weaker effects, while they significantly affect company performance. This paper provides a model for leaders in halal industry to enhance their business activities based on supply chain orientation elements to improve company performance.